Poverty in Egypt 2008-09 : Withstanding the Global Economic Crisis - World Bank (Washington, DC, 2013)
The original aim of this poverty analysis, prepared in collaboration with Egypt's Ministry of Economic Development, was to help inform the country's development strategy and guide World Bank assistance in support of that strategy over the coming years. This objective remains nevertheless valid, although the timeframe for addressing some of the most critical issues, such as the high rate of extreme poverty, vulnerability, and food insecurity may now be accelerated. The authors believe that the analysis presented in this note, while being based on data that precede the actual onset of the current political crisis, reveals deep tensions in the society that are linked to the high level of vulnerability and the lack of an efficient and flexible social assistance system. This report assesses the poverty and welfare changes in Egypt between 2008 and 2009 and presents a comprehensive picture of the evolution of poverty between 2004/05 and 2008/09. Poverty in Egypt decreased between 2005 and 20082, due in large part to rapid economic growth, although high inflation during this period had detrimental effects on the extreme poor. Yet, the sudden economic slowdown in the context of accelerating inflation in 2008/2009 reversed the gains in poverty reduction achieved during the period of rapid growth. The increase in poverty closely followed the accelerating inflation during 2008 causing vulnerable groups to be particularly affected by the economic turbulence. Despite these setbacks, some of the gains from the rapid growth between 2005 and 2008 were sustained over the crisis period. Policies aimed at helping households withstand the effects of the crisis were however not sufficient to prevent an increase in poverty. The crisis exposed underlying vulnerabilities in Egypt s social protection system. Finally, the adverse effects of food price shocks on the real incomes of Egypt s poor point to the need for further analytical work on labor markets, in particular wage policy, as part of the social risk management framework.